What determines FinTech success?—A taxonomy-based analysis of FinTech success factors - Oliver Werth; Davinia Rodríguez Cardona; Albert Torno; Michael H. Breitner; Jan Muntermann (Electronic Markets, 2023)
Value creation in the financial services sector has been fundamentally transformed by digitally born financial technology (FinTech) companies. FinTech companies synthesize information systems with financial services. Given its disruptive power, the FinTech phenomenon has received great attention in academic research, practice, and media. Still, limited systematic research provides a structure and holistic view of FinTechs' success. Aiming to enhance understanding of the factors enabling FinTech success, we classify success factors across extant scientific literature on distinct FinTech business model archetypes. Our analysis reveals that the "cost–benefit dynamic of the innovation," "technology adoption," "security, privacy, and transparency," "user trust," "user-perceived quality," and "industry rivalry" are crucial factors for FinTech success and can be seen as "grand challenges" for the FinTech ecosystem. In addition, we validate and discuss our findings with real-world examples from the FinTech industry and two interviews with stakeholders from the FinTech ecosystem. Our study contributes to the knowledge of FinTechs by providing a classification system of success factors for practitioners and researchers.
Keywords: G29; O33; O39; 620; FinTech success factors; Taxonomy-based analysis; FinTech business models